Adjunctive Magnetic Seizure Therapy for Schizophrenia: A Systematic Review - Zhang, Xin-Yang; Chen, Huo-Di; Liang, Wan-Nian; Yang, Xin-Hu; Cai, Dong-Bin; Huang, Xiong; Huang, Xing-Bing; Liu, Cheng-Yi; Zheng, Wei (Frontiers in Psychiatry, 2022)
Objective: The efficacy and safety of adjunctive magnetic seizure therapy (MST) for patients with schizophrenia are unclear. This systematic review was conducted to examine the efficacy and safety of adjunctive MST for schizophrenia. Methods: Chinese (WanFang and Chinese Journal Net) and English (PubMed, EMBASE, PsycINFO, and the Cochrane Library) databases were systematically searched. Results: Two open-label self-controlled studies (n = 16) were included and analyzed in this review. In these studies, the Positive and Negative Syndrome Scale (PANSS) total scores and Brief Psychiatric Rating Scale (BPRS) total scores significantly decreased from baseline to post-MST (all Ps < 0.05), without serious adverse neurocognitive effects. Mixed findings on the neurocognitive effects of adjunctive MST for schizophrenia were reported in the two studies. A discontinuation rate of treatment of up to 50% (4/8) was reported in both studies. The rate of adverse drug reactions (ADRs) was evaluated in only one study, where the most common ADRs were found to be dizziness (25%, 2/8) and subjective memory loss (12.5%, 1/8). Conclusion: There is inconsistent evidence for MST-related adverse neurocognitive effects and preliminary evidence for the alleviation of psychotic symptoms in schizophrenia.